RURAL TOURISM DESTINATION COMPETITIVENES OF KUBAH NATIONAL PARK IN SARAWAK: TOURISTS' PERSPECTIVE - Fung-Yee Law,; May-Chiun Lo, (Asian Academy of Management Journal, 2016)
This paper argues that tourism initiatives introduced in Malaysia's rural setting lack of adequate attentions on tourists' perceptions when designing a competitive paradigm for their development and management. This paper proposes a competitive model to evaluate important factors that link to destination competitiveness. The elements of destination competitiveness investigated in this study include natural resources, range of activities, accessibility of destination and local communities. SmartPLS 2.0 (M3) is applied in this study to analyse the data collected based on path modelling and then bootstrapping. A total of 103 questionnaires collected back from Kubah National Park by using convenience sampling technique. Based on the result, natural resources, range of activities and accessibility have a significant influence on destination competitiveness. However, local communities were found not significantly influence on destination competitiveness. The results of this study are believed to contribute to tourism authorities in choosing the right tourism development paradigms in specific rural areas.